2015
DOI: 10.1016/j.amepre.2015.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Post-treatment Neurocognition and Psychosocial Care Among Breast Cancer Survivors

Abstract: Introduction Chemotherapy for breast cancer has been associated with cognitive problems; however, the impact of adjuvant hormone therapy is less clear. No studies have explored provider discussions about cognitive concerns or factors associated with neurocognitive treatment. This study examined cognitive problems, factors associated with having a provider discussion, and receipt of neurocognitive treatment. Methods Female breast cancer survivors (N=2,537) from the Sister Study and the Two Sister Study who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 30 publications
2
47
0
2
Order By: Relevance
“…Survey respondents included in the current study were women diagnosed with breast cancer who were enrolled in the Sister Study, a cohort of initially breast cancer-free women whose sister had been diagnosed with breast cancer. The design and inclusion criteria of the Sister Study have been described elsewhere [15]. This survey was approved by the Institutional Review Board of the NIEHS/NIH as an amendment to the protocol for the Sister Study.…”
Section: Methodsmentioning
confidence: 99%
“…Survey respondents included in the current study were women diagnosed with breast cancer who were enrolled in the Sister Study, a cohort of initially breast cancer-free women whose sister had been diagnosed with breast cancer. The design and inclusion criteria of the Sister Study have been described elsewhere [15]. This survey was approved by the Institutional Review Board of the NIEHS/NIH as an amendment to the protocol for the Sister Study.…”
Section: Methodsmentioning
confidence: 99%
“…Even if the prevalence of cognitive dysfunction in women with breast cancer is lower than anticipated, clinicians, researchers, and patients are still concerned about the long-term adverse effects of breast cancer treatment. For example, in a recent report on cognitive function for women with breast cancer, 60 % of female breast cancer survivors ( N = 2296) who were at least 1 year post-treatment self-reported cognitive problems after treatment (Buchanan et al 2015), highlighting the importance of research in this area. Other similar reports have consistently shown that cognitive dysfunction is one the “most feared” long-term sequela of cancer treatment (find this reference) (Myers 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to growing concern among cancer patients about cognitive impairment [65, 56], it is important to comment on potentially efficacious interventions to ameliorate hormone therapy-induced cognitive impairment, even if somewhat premature. A recent review of the clinical and basic studies suggested that exercise may be beneficial for treating hormone therapy-induced cognitive impairments in women treated for breast cancer [66].…”
Section: Discussionmentioning
confidence: 99%